Analisis Strategi Peningkatan Literasi Keuangan Syariah di Masyarakat: Studi Kasus Kecamatan Aek Bilah - S Ritonga Ari Putri; Nurwani Nurwani; Laylan Syafina (Journal of Economics and Management Scienties, 2026)
The problem of this research is the low level of Islamic financial literacy among the community in Aek Bilah District, which is influenced by limited access to Islamic financial services, minimal education, and limited information and supporting infrastructure. This study aims to identify these obstacles and recommend effective literacy improvement strategies. The study used a descriptive qualitative method. The research location was Aek Bilah District with nine key informants, consisting of one village head, one hamlet head, two business owners, and five members of the general public. To broaden the research picture, additional respondents were also involved through questionnaire distribution. The research objects included community understanding of Islamic finance, sources of obstacles, and strategies for improving literacy in the local environment. Data collection techniques used triangulation through observation, structured in-depth interviews, documentation, and questionnaires via Google Forms. The results showed that obstacles to improving Islamic financial literacy, namely low public understanding, were influenced by limited services, educational gaps, obstacles to access to information, local cultural habits, and minimal socialization from financial institutions and the government. Therefore, the recommended strategy is to expand Islamic financial services, strengthen structured outreach, provide education based on age and education level segments, and involve religious and community leaders.